2013
DOI: 10.1021/jo302830r
|View full text |Cite
|
Sign up to set email alerts
|

Trialkyl Phosphites and Diaryliodonium Salts as Co-initiators in a System for Radical-Promoted Visible-Light-Induced Cationic Polymerization

Abstract: Trialkyl phosphites ((RO)3P) can act as co-initiators for the diaryliodonium-induced cationic polymerization of cyclohexene oxide (CHO) or THF. A radical initiation step is also required, consistent with the essential role of a radical chain reaction of the phosphite with the iodonium salt to form polymerization-starting aryltrialkoxyphosphonium salts (ArP(+)(OR)3). We used the visible photolysis of phenylazoisobutyronitrile (PAIBN) as the radical initiation step. The presence of multiple fluorine substituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Later studies revealed that modification of phosphites with halogen-substituted alkoxy groups reducing their nucleophilicity could suppress any inhibitory activity of phosphite compounds to allow an efficient polymerization process (Scheme 15). 216 Promotion of cationic polymerization by free radicals produced by Type II photoinitiators has been investigated. As Type II photoinitiators thioxanthone, benzophenone, and camphorquinone and related structures have been employed in this connection.…”
mentioning
confidence: 99%
“…Later studies revealed that modification of phosphites with halogen-substituted alkoxy groups reducing their nucleophilicity could suppress any inhibitory activity of phosphite compounds to allow an efficient polymerization process (Scheme 15). 216 Promotion of cationic polymerization by free radicals produced by Type II photoinitiators has been investigated. As Type II photoinitiators thioxanthone, benzophenone, and camphorquinone and related structures have been employed in this connection.…”
mentioning
confidence: 99%
“…The thermal latent catalysis polymerization of CHO is widely used in industry, but it often has a poor polymerization yield, and the catalysts usually require tedious multistep process to synthesize. Considerable efforts have been devoted to finding new catalysts with improved CHO polymerization yield . Onium compounds (eg, iodonium, pyridinium, and sulfonium salts) and metal complexes have been reported to show catalytic activity when aided by light and/or a cocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been devoted to finding new catalysts with improved CHO polymerization yield. [9][10][11][12][13][14][15][16][17][18][19] Onium compounds [9][10][11][12][13][14][15] (eg, iodonium, pyridinium, and sulfonium salts) and metal complexes 16,17 have been reported to show catalytic activity when aided by light and/or a cocatalyst.…”
Section: Introductionmentioning
confidence: 99%